The Uptake, Trafficking, and Biodistribution of Bacteroides thetaiotaomicron Generated Outer Membrane Vesicles - Jones, Emily J.; Booth, Catherine; Fonseca, Sonia; Parker, Aimee; Cross, Kathryn; Miquel-Clopés, Ariadna; Hautefort, Isabelle; Mayer, Ulrike; Wileman, Tom; Stentz, Régis; Carding, Simon R. (Frontiers in Microbiology, 2020)
Gram-negative bacteria ubiquitously produce and release nano-size, non-replicative outer membrane vesicles (OMVs). In the gastrointestinal (GI-) tract, OMVs generated by members of the intestinal microbiota are believed to contribute to maintaining the intestinal microbial ecosystem and mediating bacteria-host interactions, including the delivery of bacterial effector molecules to host cells to modulate their physiology. Bacterial OMVs have also been found in the bloodstream although their origin and fate are unclear. Here we have investigated the interactions between OMVs produced by the major human gut commensal bacterium, Bacteroides thetaiotaomicron (Bt), with cells of the GI-tract. Using a combination of in vitro culture systems including intestinal epithelial organoids and in vivo imaging we show that intestinal epithelial cells principally acquire Bt OMVs via dynamin-dependent endocytosis followed by intracellular trafficking to LAMP-1 expressing endo-lysosomal vesicles and co-localization with the perinuclear membrane. We observed that Bt OMVs can also transmigrate epithelial cells via a paracellular route with in vivo imaging demonstrating that within hours of oral administration Bt OMVs can be detected in systemic tissues and in particular, the liver. Our findings raise the intriguing possibility that OMVs may play an integral role in microbiota-host communication systems.